2022
DOI: 10.3390/nano12142345
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Nature of Metals and Metal-Based Materials in Inactivation of Viruses

Abstract: In response to the enormous threat to human survival and development caused by the large number of viruses, it is necessary to strengthen the defense against and elimination of viruses. Metallic materials have been used against viruses for thousands of years due to their broad-spectrum antiviral properties, wide sources and excellent physicochemical properties; in particular, metal nanoparticles have advanced biomedical research. However, researchers in different fields hold dissimilar views on the antiviral m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 193 publications
0
5
0
Order By: Relevance
“…Metal nanoparticles as photocatalysts have attracted a lot of research interest recently. Among those metal-based materials, copper nanoparticles (Cu NPs) are considered to be a promising photocatalyst and have been proved to have a good bactericidal effect because their narrow band gap can realize visible light absorption. , Kumar et al applied a shellac/CuNPs hybrid nanocoating to surgical masks, thus enhancing the surface hydrophobicity of the masks. Meanwhile, the developed coating surface exhibited superior photocatalytic antimicrobial activity, endowing the mask with reusable and self-disinfecting capabilities (Figure A) …”
Section: Classification Of Photocatalytic Antimicrobialsmentioning
confidence: 99%
“…Metal nanoparticles as photocatalysts have attracted a lot of research interest recently. Among those metal-based materials, copper nanoparticles (Cu NPs) are considered to be a promising photocatalyst and have been proved to have a good bactericidal effect because their narrow band gap can realize visible light absorption. , Kumar et al applied a shellac/CuNPs hybrid nanocoating to surgical masks, thus enhancing the surface hydrophobicity of the masks. Meanwhile, the developed coating surface exhibited superior photocatalytic antimicrobial activity, endowing the mask with reusable and self-disinfecting capabilities (Figure A) …”
Section: Classification Of Photocatalytic Antimicrobialsmentioning
confidence: 99%
“…Metals such as copper and zinc possess several properties including redox, photocatalytic, and structural stability, along with antibacterial and antiviral properties [142], that suggest that their use as antiviral agents in virus-contaminated swine feeds is worth exploring. Copper ions, alone or in copper complexes, have potent antibacterial and antiviral activity [143].…”
Section: Copper and Zincmentioning
confidence: 99%
“…Wei et al [145] compared the antiviral effects of zinc chloride and zinc sulfate when applied to swine testicle cells infected with TGEV and showed that although these zinc salts had no effect on TGEV-cell binding, antiviral effects were observed through the inhibition of virus penetration or exit or the intracellular phase of the TGEV life cycle. Although the chemical structures of metals such as copper and zinc affect their ability to inactivate viruses, their redox capability appears to be a key chemical component affecting antiviral activity [142]. Furthermore, the use of copper and zinc nanoparticles may not only provide direct antiviral activity but may also provide therapeutic effects on animals infected with viruses [142].…”
Section: Copper and Zincmentioning
confidence: 99%
See 1 more Smart Citation
“…Using self-disinfecting face masks , or surfaces is a convenient and effective approach to control the spread of infections while reducing exposure to disinfectant products, which may cause health problems . Currently available self-disinfecting methods , rely on external factors such as heat or light or may not offer rapid disinfection, making them inconvenient or impractical for on-demand use. Hence, achieving rapid and effective antipathogenic performance is essential when developing self-disinfecting coatings.…”
Section: Introductionmentioning
confidence: 99%